Fertility defects in Surfactant associated protein D knockout female mice: altered ovarian hormone profile. (March 2016) - Kay, Sharon; Madan, Taruna
Highlights: Sftpd deficiency in mice affects female fertility, with increased pre-implantation embryo loss. Altered ovarian hormone profile with aberrant uterine expression of hormone responsive genes in Sftpd knockout mice. Dysregulated immune profile in pre-implantation uteri of Sftpd knockout mice. Novel roles for SFTPD in female reproductive tract, beyond host defense. Abstract: Surfactant associated protein D (SFTPD, also known as SP-D), a pattern recognition molecule, is an integral component of the mucosal immune system of female reproductive tract (FRT). In addition to host defense functions in the FRT, recent evidences indicate immunomodulatory role of SFTPD in parturition and pre-term labor. Regulation of SFTPD expression by ovarian hormones in the mouse uterus implicates SFTPD of FRT in pregnancy establishment and maintenance. In the current study, we attempted to decipher the functional relevance of SFTPD in FRT by characterizing the fertility parameters of surfactant associated protein D knockout ( Sftpd tm1Jhf / Sftpd tm1Jhf ) female mice. Knockout female mice exhibited extended estrous cycle with altered serum profile of ovarian hormones. We also demonstrate altered expression of ovarian hormone receptors and hormone responsive genes ITGB1, LIF and HOXA10 in uteri of these mice. Knockout females mated with wild type males had significantly smaller litter size due to increased pre-implantation embryo loss. We also observed an altered immune profile in knockout mice uteri with elevated levels of inflammatory cytokines, increased numbers of pro-inflammatory monocytes/macrophages and lower FOXP3 levels during the pre-implantation period. LPS administration to pregnant knockout mice did not result in any increase in embryo implantation loss and was associated with a blunted uterine pro-inflammatory response, plausibly due to higher levels of serum progesterone. Taken together, our results demonstrate that SFTPD deficiency affects female fertility, highlighting roles for SFTPD in ovarian and uterine physiology.